Corneal sub‐basal whorl‐like nerve plexus: a landmark for early and follow‐up evaluation in transthyretin familial amyloid polyneuropathy. (24th October 2020) - Zhang, Y.; Liu, Z.; Zhang, Y.; Wang, H.; Liu, X.; Zhang, S.; Liu, X.; Fan, D.
Abstract : Background and purpose: Small‐fiber nerves are the first to be involved in transthyretin familial amyloid polyneuropathy (TTR‐FAP) patients. In vivo corneal confocal microscopy (CCM) is a noninvasive technique to detect small‐fiber polyneuropathy (SFN) by quantifying corneal nerve morphology. The characteristic whorl‐like pattern of the corneal nerve provides a static landmark for observation. We aimed to evaluate whether CCM images of the whorl‐like plexus can sensitively evaluate and monitor disease progression in FAP patients. Methods: Fifteen FAP patients and 15 controls underwent neurological evaluation and CCM observation. Corneal nerve fiber length (CNFL), corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD) detected by conventional method and inferior whorl length (IWL), inferior whorl fiber density (IWFD), and inferior whorl branch density (IWBD) were compared in controls and patients. The Langerhans cell (LC) density in each image was calculated. Results: All CCM parameters were significantly reduced with disease progression. Preclinical patients had significantly lower IWL ( P = 0.008) than age‐matched controls. IWL ( P = 0.006), CNFL ( P = 0.005), CNBD ( P = 0.008), and CNFD ( P = 0.014) were significantly lower in early‐phase patients. LC density was significantly increased around the central whorl in early‐phase patients and was relatively lower in progressive patients. Both IWL and CNFL correlated with the severity of neuropathy, and IWL was more significantly reduced. The area under the receiver operating characteristic (ROC) curve for FAP with CNFL and IWL was 88.0% (95% CI, 70.9%–96.9%) and 89.3% (95% CI, 72.6%–97.6%), respectively, exceeding other parameters. Conclusions: IWL is a more sensitive surrogate to detect preclinical SFN in FAP and can best discriminate patients from controls. The clustering of immature LCs at the inferior whorl area might reflect the inflammatory response of small‐fiber nerves at the early stage. Abstract : Measurements of the corneal whorl‐like nerve plexus by using corneal confocal microscopy (CCM) is a sensitive biomarker to detect small‐fiber neuropathy of transthyretin familial amyloid polyneuropathy (TTR‐FAP) patients in an early stage. The whorl‐like pattern of the corneal nerve also provides a static landmark to monitor disease progression.